STEAM approach to enhance the creativity of students with special needs in inclusive primary schools - Siska Angreni; Rona Taula Sari; Fadhilla Mursyafiela (Universitas Ahmad Dahlan, 2023)
This research is motivated by the lack of 21st-century skills, especially among students with special needs in the slow learner category. The study aims to enhance students' creativity in learning science by implementing the STEAM approach in class VD of Elementary School 24 Ujung Gurun. This research follows the classroom action research method, conducted in two cycles, with each cycle comprising two meetings. The process involves four essential stages: planning, implementation, observation, and reflection. The research employed teacher observation sheets and student creativity observation sheets as instruments. The data analysis technique used is comparative descriptive statistical analysis, comparing learning creativity between cycle I and cycle II. The specific creativity indicator observed is elaboration, with sub-indicators focusing on developing or enriching other people's ideas. The results indicate that the application of the STEAM approach led to an increase in the creativity of students with special needs. The observation and data analysis results demonstrate a rise in students' creativity from an average of 64% in cycle I to 81% in cycle II. In conclusion, the study revealed an improvement in the creativity of students with special needs through the implementation of the STEAM approach at Primary School 24 Ujung Gurun. Despite challenges such as assessing work based on student's abilities and some students lacking honesty in their efforts, it is recommended to continue using the STEAM approach as an alternative method to enhance the creativity of slow learners in learning, given its positive impact on students' creative abilities.